Walking in My Students’ Shoes: An ESL Teacher Brings Theory to Life in Order to Transform Her Classroom - Mary Amanda Stewart (Networks: An Online Journal for Teacher Research, 2010)
Throughout my career as an English as a Second Language (ESL) teacher, it has been obvious that in each setting there is a popular phrase that accurately describes the classroom: “one of these things is not like the other” – and it’s the teacher! Yes! It is I who stands alone as the native English speaker in almost every class I have ever taught. I was a teacher assistant in an elementary school, an ESL and math teacher at the middle school level, and an adult education teacher at a community college for a total of 9 years. In each and every context I have been completely different from my students in regards to native language and culture. Of course, that is the case in many ESL contexts, but it began to strike me as odd when I started teaching undergraduate pre-service teachers at a university about how to teach English Language Learners (ELL students). I suddenly had 30 faces peering up at me, the ESL “guru,” waiting for me to enlighten them regarding theory, methodology, and best practices for teaching ELL students. I was the presumed expert on teaching a population of which I am not a member and who have experiences that I do not share. It occurred to me that in order to better my understanding of teaching ELL students, I had to recreate their experience in my own life as closely as possible. I decided to purposely engage in my own second language learning experience and take a walk in my students’ shoes.